Evaluasi Model Tyler pada Permainan Stairs & Cigarettes terhadap Pemahaman Bahaya Merokok: Evaluation of Tyler's Model on the Stairs & Cigarettes Game on Understanding the Dangers of Smoking - Zahratul Raudah; Nina Permata Sari; M. Andri Setiawan (ITScience (Information Technology and Science), 2025)
Smoking behavior among adolescents remains a serious problem in the health and education sectors. The low level of students' understanding of the dangers of smoking indicates the need for educational media that can actively involve students in guidance and counseling services. The Stairs & Cigarettes game was developed as an educational game to improve understanding of the dangers of smoking, but its implementation needs to be evaluated systematically. This study aims to evaluate the implementation of the Stairs & Cigarettes game using the Tyler evaluation model by examining the suitability of the objectives formulation, implementation conditions, measurement techniques, and the comparison of pre-test and post-test results regarding understanding the dangers of smoking among adolescents. The study employed a mixed-methods approach with an evaluation research design. The subjects were 34 students of grades X-F of SMA Negeri 9 Banjarmasin. Qualitative data were obtained through interviews with guidance and counseling teachers and analysis of RPL documents.In contrast, quantitative data were collected through pre- and post-test questionnaires assessing understanding of the dangers of smoking, based on the Health Belief Model. Data analysis was conducted using descriptive statistics and a paired-samples t-test. The results showed that the formulation of objectives, the implementation context, the measurement techniques, and the comparison of results were consistent with the principles of the Tyler evaluation model. There was a significant increase in students' understanding of the dangers of smoking after participating in classical guidance services using the educational game Stairs & Cigarettes (p < 0.001). The implementation of the game Stairs & Cigarettes was in accordance with the service's objectives and has the potential to serve as an alternative medium for guidance and counseling, helping increase adolescents' understanding of the dangers of smoking.